The development of Eudragit® NM-based controlled-release matrix tablets - Dvořáčková, Kateřina; Kalėdaitė, Rasa; Gajdziok, Jan; Rabišková, Miloslava; Bajerová, Martina; Muselík, Jan; Lažauskas, Robertas; Pečiūra, Rimantas; Bernatonienė, Jurga (Medicina (Kaunas, Lithuania), 2012)
UNLABELLED: Eudragit® NM was investigated as a matrix former in combination with microcrystalline cellulose as an insoluble filler for preparing controlled-release tablets containing model drugs with different solubility. MATERIAL AND METHODS: Three sets of matrix tablets differing in the drug-to-filler ratio (1:1, 2:1, and 4:1) and polymer amount with diltiazem hydrochloride (freely soluble) or caffeine (sparingly soluble) were prepared. Samples were evaluated by the dissolution test at pH 6.8 corresponding to the upper part of the small intestine; the selected samples were tested at a changing pH level to better simulate in vivo conditions. RESULTS: The prepared matrix tablets fulfilled all the requirements of the European Pharmacopoeia. Tablets with Eudragit® NM showed excellent mechanical characteristics. In vitro studies showed that the set 1:1 was the most suitable for the sustained release of a freely soluble drug concerning the burst effect and the total drug amount released within 12 hours. The significant effect of the drug-to-filler ratio and polymer amount on the dissolution profile was confirmed by similarity factor analysis. A faster drug release was observed during the dissolution test within changing pH levels because of the pH-dependent solubility of diltiazem. A prolonged release of the sparingly soluble drug was not achieved, and a trend for fast disintegration was observed. CONCLUSIONS: The combination of Eudragit®NM with microcrystalline cellulose as an insoluble filler seems to be suitable only for freely soluble drugs, when the amount of the drug and the filler is similar.
Keywords: kyseliny polymethakrylové; Drug Design; Polymethacrylic Acids; léky s prodlouženým účinkem; celulosa; Delayed-Action Preparations; racionální návrh léčiv; Cellulose; Solubility; Tablets; tablety; rozpustnost